Mechanisms for developing universities according to the QS global ranking standard - field research at the University of Kufa - ايثار عبد الهادي آل فيحان,; قاسم محمد مظلوم, (Iraqi Journal for Administrative Sciences, 2025)
This research came in an attempt to apply international academic classification standards that are based on the principles of quality education in order to maintain or improve the ranking of universities according to the international classification, which requires providing a database that facilitates the process of conformity with the standards and facilitates the arrangement of these organizations, including (university, college, institute, department). Scientific) according to its performance levels leading to diagnosing and treating the negative and positive aspects towards achieving rapprochement with corresponding universities in countries of the world.